(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In the MSME (Micro, Small and Medium Enterprises) sector, bad asset management (NPA) is crucial to maintaining liquidity and profitability. NPA refers to loans or advances that do not generate an expected return due to default or late repayment .N.P.A are the indicator to assess the health of the financial sector. This paper tries to present a review of 50 papers. With this literature review paper we are trying to find out the gap analysis after studying the research work on non performing asset, profitability, liquidity and A.I. to analyze the N.P.A arises in the msme sector.